2016
DOI: 10.1021/acs.jmedchem.5b01875
|View full text |Cite
|
Sign up to set email alerts
|

A Real-World Perspective on Molecular Design

Abstract: We present a series of small molecule drug discovery case studies where computational methods were prospectively employed to impact Roche research projects, with the aim of highlighting those methods that provide real added value. Our brief accounts encompass a broad range of methods and techniques applied to a variety of enzymes and receptors. Most of these are based on judicious application of knowledge about molecular conformations and interactions: filling of lipophilic pockets to gain affinity or selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
107
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(113 citation statements)
references
References 72 publications
1
107
0
1
Order By: Relevance
“…The resulting structural proposal clearly revealed a chalcogen bond from the benzothiophene donor to the backbone C=O of Asn66 as acceptor (Figure ). The position of this backbone C=O is highly conserved in co‐crystal structures of hCatL, which makes it entropically a favorable interaction partner . The interaction occurs at a distance d (S⋅⋅⋅O=C)=3.5 Å and at an angle α (O⋅⋅⋅S−C)=158°, well within the range of chalcogen bonds observed in other protein‐ligand complexes (Figure ) .…”
Section: Resultsmentioning
confidence: 63%
“…The resulting structural proposal clearly revealed a chalcogen bond from the benzothiophene donor to the backbone C=O of Asn66 as acceptor (Figure ). The position of this backbone C=O is highly conserved in co‐crystal structures of hCatL, which makes it entropically a favorable interaction partner . The interaction occurs at a distance d (S⋅⋅⋅O=C)=3.5 Å and at an angle α (O⋅⋅⋅S−C)=158°, well within the range of chalcogen bonds observed in other protein‐ligand complexes (Figure ) .…”
Section: Resultsmentioning
confidence: 63%
“…[64] As elegantly described by Kuhn et al,s ulfonamides can be considered as "molecular chimeras, which are found to form hydrogen bonds as wellasi nteract with unipolar environmentsw ithin proteins". [8] We were interested in improvingt he binding affinities in our class of inhibitors by harvesting favorable nonpolarc ontacts with residues such as Lys139, Val141, Ser263,a nd Pro267a t the exit of the pABAc hannel (Supporting Information, Section S5, Figures S13 and S14). We implemented as ulfonamide group into as eries of extended derivatives (AE)-9-17 to properly orient the terminal lipophilic moieties.…”
Section: Aryl Sulfonamide/aryl Sulfone Seriesmentioning
confidence: 99%
“…[1][2][3] Docking and modeling of protein-ligand interactions have become ac ommon routine to prioritize ideas for synthesis. [6,7] Some reports suggest to set the threshold for the bioactive conformation at 3kcal mol À1 of the loweste nergy conformation, [6,8] whereas others give am aximum Gibbs energy differenceo f5kcal mol À1 . [4,5] Ad ifference in conformational energyb etween free and bound state of DDG unbound!bound % 1.4 kcal mol À1 already translates into at enfoldd ecrease in Gibbsb inding energy.…”
Section: Introductionmentioning
confidence: 99%
“…Methods to predict the binding mode of a ligand, that is, molecular docking, have attempted to account for conformationally flexible regions of the protein to move during docking (i.e., induced‐fit docking) or by using multiple predefined protein structures with relevant conformations (i.e., ensemble docking). Another strategy to simulate induced fit, is to constrain most of the protein structure and selectively relaxing selected binding site residues that tend to be mobile . Prospective identification of these flexible residues, however, without multiple X‐ray structures can be challenging.…”
Section: Introductionmentioning
confidence: 99%